Ketahanan Pangan Rumah Tangga Anak Stunting Usia 6-23 Bulan di Wilangan, Kabupaten Nganjuk - Dessy Nur Fadzila; Edy Purwanto Tertiyus (Amerta Nutrition, 2019)
Background: Children under two years are susceptible to nutritional problems. Nutritional problems can be caused directly by nutritional intake and infection. Nutritional intake can be affected by conditions of household food security. Household food insecurity can be caused by insufficient food availability which causes a lack of nutritional intake.Objectives: To analyze the condition of household food security with stunted and non-stunted children aged 6-23 months in Wilangan, Nganjuk District.Methods: This study was an observational and used case-control design. The subject of this study were 72 children aged 6-23 months in Wilangan, Nganjuk District obtained from the simple random sampling method. The samples of case group were 36 children and control group were 36 children. The United Stated Household Food Security Survey Module (US-HFSSM) questionnaire was used to measure household food security, and anthropometric measurements of body length. The data analysis used by spearman and chi-squared statistical test.Results: Majority of non-stunted children was in household food security (75.0%). The stunted children in household food insecurity was higher than non-stunted children (41.7%). This study showed there was no significant correlation between family characteristics with stunted. But, there was a correlation between the age of children under two years old (p=0.02) and household food security status (p=0.041) with stunted. Conclusions: Household with food insecurity have a higher risk stunted than household with food security.ABSTRAKLatar Belakang: Anak yang berusia dibawah dua tahun rentan mengalami masalah gizi. Masalah gizi dapat disebabkan oleh asupan gizi yang dipengaruhi ketahanan pangan. Rumah tangga yang mengalami rawan pangan dapat disebabkan oleh ketersediaan pangan yang kurang sehingga menyebabkan kurangnya asupan gizi.Tujuan: Menganalisis kondisi ketahanan pangan rumah tangga dengan stunting dan non-stunting pada anak usia 6-23 bulan di Kecamatan Wilangan, Kabupaten Nganjuk.Metode: Jenis penelitian yaitu observasional dan menggunakan desain penelitian kasus kontrol. Subjek dari penelitian ini adalah anak berusia 6-23 bulan di Wilangan Kabupaten Nganjuk sebanyak 72 baduta yang didapatkan dari metode simple random sampling. Sampel kelompok kasus sebanyak 36 baduta dan kelompok kontrol sebanyak 36 baduta. Kuesioner United Stated-Household Food Security Survey Module (US-HFSSM) digunakan untuk mengukur ketahanan pangan rumah tangga, dan pengukuran antropometri panjang badan. Uji statistik menggunakan spearman dan chi-square.Hasil: Sebagian besar baduta non-stunting berada pada rumah tangga yang tahan pangan (75,0%). Baduta stunting yang berada pada rumah tangga yang rawan pangan lebih tinggi daripada baduta non-stunting (41,7%). Penelitian ini menunjukkan hasil tidak terdapat korelasi yang signifikan antara karakteristik keluarga dengan stunting, namun terdapat korelasi antara usia baduta  (p=0,02) dan ketahanan pangan rumah tangga (p=0,041) dengan stunting.Kesimpulan: Rumah tangga yang mengalami rawan pangan berisiko stunting lebih tinggi daripada rumah tangga yang tahan pangan.